A hierarchical energy management system for multiple home energy hubs in neighborhood grids. (March 2020) - Gholinejad, Hamid Reza; Loni, Abdolah; Adabi, Jafar; Marzband, Mousa
Abstract: This paper presents a hierarchical energy management system (HEMS) for multiple home energy hubs in the neighborhood grid (MHEHNG). The main objectives are maximizing financial profit and shaving the peak of upstream grid. This way, the proposed HEMS manages the energy generation and energy storing, as well as energy purchase/sale of each home energy hub (HEH) under the two levels including lower and upper levels. The lower level is responsible for supplying the internal load and reducing the energy cost in each HEH. The upper level is the central energy management system (CEMS) which is focused on forming a coalition between the local HEHs, as well as giving the tempting offers to increase the financial profit through a heuristic bidding strategy. The principle of proposed bidding strategy is based on weighted distributing of excess power among consumers that is one of the contribution of this paper. It leads to trading more energy at the lowest possible price. Determining the most appropriate operational scenario in each HEH requires the investigation of both technical and financial aspects. A novel scenario selector method has been proposed based on SOC-tariff plane. This is another contribution of this work. A simulator has been implemented in the MATLAB/GUI software environment to facilitate the evaluation of proposed HEMS performance. The simulation results indicate the effectiveness of the proposed HEMS. They show a decrease in the total energy cost of the CBs by almost 9.4%, and an increase in the total profit of the HEHs by 4.55%. Also, it was found out that the energy can be purchased from HEHs at varying rates and can be sold to the consumers at almost constant rates by using the proposed bidding strategy. This motivates HEHs to submit more power at lower tariffs to the CEMS. Highlights: Developing a simulator for implementing Hierarchical Energy Management System (HEMS). Presenting heuristic bidding strategy for HEMS. Presenting a HEMS for several Home Energy Hubs in the neighborhood grid .